Pathways of continuity and change: diversification, intensification and mobility in Maasailand, Kenya - BurnSilver, Shauna B., author; Galvin, Kathleen A., advisor (Colorado State University. Libraries, 2007)
In recent decades multiple drivers have been acting on Maasai pastoralists in the Greater Amboseli Ecosystem (GAE). The Kenyan government and international policymakers have made a systematic effort to modernize the Kenyan pastoral sector based on prescriptions of livestock intensification and a process of land tenure change that moves herders from communal land use to privatized land ownership. Additional drivers including population growth, competition for territory, greater engagement in the Kenyan economy, and frequent drought, are also pushing and pulling pastoralists to adjust their livelihood strategies. These drivers have created an atmosphere of unprecedented change in Maasailand, Kenya -- a situation with negative implications for pastoral well-being and resilience. How pastoral households cope with these challenges is the central question of this PhD study. Three key responses are identified and analyzed: economic diversification, livestock intensification and livestock mobility.

I demonstrate that economic diversification and intensification of livestock production strategies are occurring in Maasailand, and address some of the underlying complexities that accompany both processes. Results show that in spite of economic diversification, livestock in Amboseli remain a critical component of pastoral livelihoods.

Previous efforts to document pastoral wealth were based almost entirely on the number of animals held per household or per capita. I develop two new indices of pastoral wealth and compare pastoral wealth status across wealth ranking methods in Amboseli. Results emphasize that while households are diversifying, rich and poor households are changing along different trajectories. This finding has implications for greater wealth stratification in this pastoral society in the future.

I also analyze the role of mobility in pastoral production, as conditions push for land privatization, but households continue to face significant climate variability and low levels of livestock infrastructure. A cultural-institutional system of grazing management in place in unsubdivided areas of the GAE seems to allow herders to access sufficient forage quantity under normal precipitation conditions, as well as forage quality in particular time periods.

Many of the changes occurring in pastoral Maasailand are common to the experiences of pastoral groups globally. As such, results from this study will contribute to an ongoing discussion regarding the future viability of pastoralism under conditions of change.
Keywords: diversification; Kenya; land tenure change; land use; Maasai pastoralism; Maasailand; mobility; pastoral livelihood strategies; pastoral wealth; remote sensing; cultural anthropology; geography; range management; research; livestock; regression analysis; trends; animals; debates; property rights; ecosystems; cattle; wildlife conservation; skills; ecology; agriculture; farmers; ranches; flexibility; variables; copyright; data collection; households; national parks; rain; animal populations; land tenure